MEASUREMENT OF THE PHOTON STRUCTURE-FUNCTION F2-GAMMA AT Q2 FROM 7 TO 70 (GEV/C)2 - Althoff, M; Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Rosskamp, P; Wallraff, W; Bock, B; Eisenmann, J; Fischer, H; Hartmann, H; Hillen, W; et al. (Springer-Verlag, 1986)
We have measured the process e+e-→e+e-+hadrons, where one of the scattered electrons was detected at large angles, with Q2 ranging from 7 to 70 (VeV/c)2. The photon structure function F2γ(x, Q2) was determined at an average Q2 of 23 (GeV/c)2. The measurements were compared to theoretical predictions of the Quark Parton Model and Quantum Chromodynamics. In both models a hadronic part was added. Within the errors the data are in agreement with the QPM using quark masses of 300 MeV/c2 for the light quarks. The data also agree with a QCD calculation including higher order corrections. A fit yielded a Mathematical expression value of 140-65+190 MeV, where the errors include statistical and systematic uncertainties. © 1986 Springer-Verlag.